Percepção e prática de orientações sobre medidas preventivas não farmacológicas para a Covid-19 na área de uma unidade básica de saúde de Campina Grande- PB - Oliveira, Maria Núbia de (2022)
The disease caused by the new coronavirus 2019 (COVID-19) has led to a serious global public health crisis that has forced the population to adopt preventive non-pharmacological measures (MNF) for work. I assume that perceptions about COVID-10 are associated with adoption of MNF. The general objective of this dissertation was to analyze how the population of the territory of a basic health unit (UBS) in the city of Campina Grande-PB perceives and applies the information on MNF for the prevention of COVID-19, as well as howto assess the relationship between This perception and sociodemographic variables and diagnosis of COVID-19. A descriptive-cross-sectional field research was carried out with a mixed quanti-qualitative approach in sequential phases. The first phase involved a sample of 70 usersfrom the population attached to UBS forthe quantitative phase and, among these, 14 selected forums for the qualitative phase. The collection of data was obtained by structured questionnaire (sociodemographic data; information on MNF; gravity of COVID 19; susceptibility to COVID-19; confidence in MNF) and by unstructured interviews addressing the confrontation, information, and impact of COVID-19. The sample of the first phase was predominantly female (65.2%), white (69.6%) and higher education/post graduation (62.3%), a profile that was also observed in the sample of 14 participants of the phase qualitative. It was observed that adherence to MNF was high, applying MNF in association, especially hand washing, use of alcohol and facial mask (51/74.2% for each) and isolation (36/52.4%). MNF was reported for the most part by TV and newspapers, and to a lesser extent by friends, relatives, government officials and UBS professionals; 49.2% felt susceptible and 65.2% felt confident in MNF. In the qualitative analysis of the two 14 participants in the second phase, there were more speeches regarding masks, vaccination, and community, in the emerging categories of prevention, perception, information, governance and impact. The respondents reported criticism of the content and insufficient emphasis on information and partial adequacy for their community. The “kit-COVID” arose in a critical tone on the allegation of non-scientificity. Foram reported above all ações de saúde de ambito hospitalar. The impact of COVID-19 occurred due to confrontation, with a negative effect on the family due to distancing, and due to the change in attitude of people not learned from the crisis. The objective of the second article was to determine the perception and application of the main guidelines on MNF for the prevention of COVID-19, and its relationship with sociodemographic variables and diagnosis of COVID-19. The data show that 47.8% were civil servants, representing 58.9% two who had paid work in the sample. It was observed that 51 participants (75%) kept their paid jobs during the pandemic, 44 (86.2%) in face-to-face mode. Adherence to the MNF was discharged, but there was an association with the perception of susceptibility to contagion and gravity of illness with sociodemographic variables and diagnosis of COVID-19. It is concluded that the orientations on the MNF will reach the participants and for this, they must have contributed or have a favorable educational degree from the sample. It was possible to understand how information about MNF was received (TV, jornais), perceived (valued and understood, but considered insufficient) and applied (maioria da amostra). It was concluded that most of the participants perceived the COVID-19 pandemic as a serious illness, demonstrating confidence in the preventive measures recommended and provided, understanding changes in social isolation forthemselves and theirfamilies as negative, as well as the impact of crise no seu pessoal growth. The sociodemographic characteristics of the sample are probably associated with their answers about the information acquired and the adoption of the MNF.